Dissipation of Emamectin Benzoate Residues in Rice and Rice-Growing Environments - Deng, Ligang (Molecules, 2020)
The experiment developed the ultra-high-performance liquid chromatography–tandem mass spectrometry (UPLC/MS/MS) method for testing emamectin benzoate, and studied the metabolism of emamectin benzoate in rice plants and rice-growing environments via application of this testing method. The dissipation curve of emamectin benzoate standard substance was good at 0.5–200 μg L(−1), and its correlation coefficient was greater than 0.99. In the concentration range of 0.1–50 μg kg(−1), the average recovery rate of plants, soil, and field water was 82 %–102 %, and relative standard deviation (RSD) was between 0.3 % and 15.9 %. Half-lives in rice plants and soil were 0.8–2.8 days and 1.9–3.8 days, respectively, and emamectin benzoate was not detected in rice or rice hull. The experiment showed that emamectin benzoate is harmless to human health at the concentration recommended by the manufacturer.